FC044: Heterozygous Variants in Kinase Domain of NEK8 cause an Autosomal-Dominant Ciliopathy. (3rd May 2022) - Claus, Laura; Stallworth, Jennifer; van Jaarsveld, Richard; Turner, Joshu; Hawks, Alexandra; May, Melanie; Flanagan-Steet, Heather; Louie, Raymond; Silver, Josh; Lerner-Ellise, Jordan; Morel, Chantal; Mighton, Chloe; et al.
Abstract: BACKGROUND AND AIMS: NEK8 / NPHP9 encodes a protein that localizes to the primary cilium. Biallelic NEK8 variants are known to cause multiorgan developmental defects, including kidney cystic dysplasia and extensive extra-renal defects, with heterozygous carrier parents being asymptomatic [1]. This autosomal recessive inheritance is the most common inheritance mode for ciliopathies. Complementary to this, we now propose a dominant negative effect for specific heterozygous NEK8 missense variants in the kinase domain resulting in an autosomal-dominant ciliopathy. METHOD: We performed genetic testing in patients from several medical centers. To explore the consequences of the identified NEK8 variants, we are performing cilia staining assays in patients' skin fibroblast and kidney cells, as well as in mIMCD3 cells overexpressing the identified variants. Furthermore, we are examining the impact of the NEK8 variants on replication stress response. RESULTS: We identified three distinct heterozygous NEK8 variants in 12 families (Table 1), all leading to missense alterations in the kinase domain. Interestingly the p.Arg45Trp variant is a recurrent variant we detected in 10 unrelated families. All patients have a kidney phenotype that varies from mild focal segmental glomerulosclerosis to prenatal presentation with polycystic kidneys. Most patients have kidney failure needing kidney replacement therapy at varying ages of onset. In all patients, we thoroughly checked whether a second variant could be found. Furthermore, the large symptomatic family and de novo occurrences favor a dominant inheritance mode. Our preliminary results from functional studies show abnormal primary cilia formation in serum-starved cells as well as increased replication stress. CONCLUSION: We present the first evidence for a pathogenic effect of heterozygous NEK8 variants. Remarkably our patients present with a kidney limited phenotype as compared to the multiorgan defects found in patients with biallelic variants. This reveals a new mode of inheritance for NEK8 variants and expands genotype-phenotype correlations for this gene.